Karl Popper: teoria ewolucji a logika sytuacji - Olczyk, Sławoj (Filozofia Nauki, 2003)
The article aims at reconstruction of a importance of Popper's situational logic to his analysis of an epistemological status of evolution theory. The paper consists of four parts. In the first one I present Popper's arguments on an epistemological status of Darwinism he exposed in „The Poverty of Historicism”. In the second part I put forward Popper's views on evolution theory in the 60-th. The third part aims at outlining of his idea of situational logic. And in the last part of this paper I consider philosophical significance of the idea to an epistemological status of Darwinism.